Inhibition of procarcinogen activating enzyme CYP1A2 activity and free radical formation by caffeic acid and its amide analogues - Paitoon Narongchai (2018)
© 2016 Bentham Science Publishers. Objectives: Caffeic acid (CAF) and its amide analogues, ethyl 1-(3’,4’-dihydroxyphenyl) propen amide (EDPA), phenethyl 1-(3’,4’-dihydroxyphenyl) propen amide (PEDPA), phenmethyl 1-(3’,4’-dihydroxyphenyl) propen amide (PMDPA) and octyl 1-(3’,4’-dihydroxyphenyl) propen amide (ODPA) were investigated for the inhibition of procarcinogen activating enzyme. Methods: CYP1A2 and scavenging activity on formation of nitric oxide, superoxide anion, DPPH radical and hydroxyl radical. Results: It was found that they inhibited CYP1A2 enzyme by uncompetitive inhibition. Apparent Ki values of CAF, EDPA, PEDPA, PMDPA and ODPA were 0.59, 0.39, 0.45, 0.75 and 0.80 _M, respectively suggesting potent inhibitors of CYP1A2. Moreover, they potentially scavenged nitric oxide radical with IC 50 values of 0.12, 0.22, 0.28, 0.22 and 0.51 mM, respectively. The IC50 values of superoxide anion scavenging were 0.20, 0.22, 0.44, 2.18 and 2.50 mM, respectively. 1, 1- diphenyl-2- picrylhydrazyl (DPPH) radical-scavenging ability, shown as IC50 values, were 0.41, 0.29, 0.30, 0.89 and 0.84 mM, respectively. Moreover, the hydroxyl radical scavenging in vitro model was shown as IC50 values of 23.22, 21.06, 17.10, 17.21 and 15.81 _M, respectively. Conclusion: From our results, caffeic acid and its amide analogues are in vitro inhibitors of human CYP1A2 catalytic activity and free radical formation. They may be useful to be developed as potential chemopreventive agents that block CYP1A2-mediated chemical carcinogenesis.